Globalization, earnings and consumer prices: Taking stock of the benefits from global economic integration - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2008)
Globalization has been accused of "stealing jobs" and depressing wages in the developed part of the world. China's entry into the world economy, in particular, has sparked fears about a "middle-class squeeze". These fears resemble the anxiety in previous eras over the rise of new emerging markets. As recent as twenty years ago, Japanese firms were by some considered to be far too competitive for American or European firms to survive. Now, as then, most of these fears are based on erroneous facts and wild exaggerations. In this new Policy Brief, Fredrik Erixon analyses data on wages, prices and income to estimate the benefits from globalization. He finds a strong link between disinflation and rising real income.
Keywords: 330; Globalisierung; Verteilungswirkung